Elitism and elite culture - Tamara Lvovna Salova (Вестник Майкопского государственного технологического университета)
The results of the investigation of the phenomenon of elite culture in the process of transition to information civilization are presented. The aim of the research is to identify the characteristics of elite culture as the antipode of mass culture. It is noted that the emergence of a class of intellectuals, the intellectual elite, influences the formation of a new type of culture: an elite intellectual culture. The concept of “elitism”, which underlies the elite culture, is considered. Ways to realize the desire for genuine elitism are proposed. The phenomenon of the expansion of the Western mosaic mass culture into the Russian cultural space through the means of mass communication, especially the Internet, is being studied. It is shown that a mosaic culture is the result of the daily impact of an abundant and random flow of random information, fleeting impressions of basic knowledge and ideas on a person, which together do not give an overall picture of the world, since a person simply does not have time to systematize and spell out the received information. It is emphasized that representatives of the intellectual elite, bearers of the elite culture, being passionaries, outstanding people, gifted, and with high moral qualities, are able to withstand the dominance of mass mosaic culture and revive the classical domestic culture model with an orderly structure of knowledge based on the national culture created by the best representatives of creative intellectuals.